2003
DOI: 10.1080/10715760310001615998
|View full text |Cite
|
Sign up to set email alerts
|

Human Red Blood Cells as A Natural Flavonoid Reservoir

Abstract: Quercetin is rapidly and avidly taken up by human red blood cells (RBC) via a passive diffusion mechanism, driven by flavonoid binding to haemoglobin and resulting in an almost quantitative accumulation of the flavonoid. Heamoglobin-free resealed ghosts accumulated quercetin exclusively in the membrane fraction. Cell-associated quercetin was biological active and could be quantitatively utilised to support the reduction of extracellular oxidants mediated by a transplasma-membrane oxido-reductase. Additional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 29 publications
2
63
0
Order By: Relevance
“…Recent studies have demonstrated that in humans flavonoids, such as quercetin and resveratrol, are readily absorbed and that their bioavailability is much greater than previously believed (Ross and Kasum 2002). Concentration of flavonoids in human plasma varies from 3 to 30 mM and certainly more if the red blood cell associated flavonoids are taken into account (Fiorani et al 2003). Interestingly, new studies in pigs report that long-term dietary intake of quercetin did not lead to a greater accumulation in any tissue compared with a single treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have demonstrated that in humans flavonoids, such as quercetin and resveratrol, are readily absorbed and that their bioavailability is much greater than previously believed (Ross and Kasum 2002). Concentration of flavonoids in human plasma varies from 3 to 30 mM and certainly more if the red blood cell associated flavonoids are taken into account (Fiorani et al 2003). Interestingly, new studies in pigs report that long-term dietary intake of quercetin did not lead to a greater accumulation in any tissue compared with a single treatment.…”
Section: Discussionmentioning
confidence: 94%
“…This fi nding supports the hypothesis that certain fl avonoids, including apigenin, may contribute to the cellular antioxidant defense system [21] or may reveal other biological effects as found in test systems (see Introduc-tion). Fiorani et al [22] found that quercetin is effi ciently taken up by human RBC via passive diffusion resulting in an accumulation of the fl avonoid in body cells. The substance was utilized as substrate for a trans-plasma membrane oxidoreductase contributing to the reduction of extracellular oxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the structural similarity between quercetin and apigenin, these results can probably be transferred to the group of fl avones as well. It has been suggested that human RBC could play a pivotal role in the distribution and bioavailability of circulating fl avonoids [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The erythrocyte has a pool of flavonic compounds, which are considered a buffer, maintaining the antioxidative activity of the erythrocyte (Fiorani et al, 2003) Quercetin and resveratrol (piceatannol) take part in the regulation of the phosphorylation of band 3 in the presence of the physiological oxidant peroxinitrite. Quercetin decreases the Syk activity and particularly prevents mediated by the free radical peroxynitrite (ONOO . )…”
Section: Changes In Phosphorylation In Oxidative Stressmentioning
confidence: 99%